Common oncogenic mutations are infrequent in oral squamous cell carcinoma of asian origin - Zanaruddin, S.N.; Yee, P.S.; Hor, S.Y.; Kong, Y.H.; Ghani, W.M.; Mustafa, W.M.; Zain, R.B.; Prime, S.S.; Rahman, Z.A.; Cheong, S.C. (Public Library of Science, 2013)
OBJECTIVES: The frequency of common oncogenic mutations and TP53 was determined in Asian oral squamous cell carcinoma (OSCC). MATERIALS AND METHODS: The OncoCarta(™) panel v1.0 assay was used to characterize oncogenic mutations. In addition, exons 4-11 of the TP53 gene were sequenced. Statistical analyses were conducted to identify associations between mutations and selected clinico-pathological characteristics and risk habits. RESULTS: Oncogenic mutations were detected in PIK3CA (5.7%) and HRAS (2.4%). Mutations in TP53 were observed in 27.7% (31/112) of the OSCC specimens. Oncogenic mutations were found more frequently in non-smokers (p = 0.049) and TP53 truncating mutations were more common in patients with no risk habits (p = 0.019). Patients with mutations had worse overall survival compared to those with absence of mutations; and patients who harbored DNA binding domain (DBD) and L2/L3/LSH mutations showed a worse survival probability compared to those patients with wild type TP53. The majority of the oncogenic and TP53 mutations were G:C > A:T and A:T > G:C base transitions, regardless of the different risk habits. CONCLUSION: Hotspot oncogenic mutations which are frequently present in common solid tumors are exceedingly rare in OSCC. Despite differences in risk habit exposure, the mutation frequency of PIK3CA and HRAS in Asian OSCC were similar to that reported in OSCC among Caucasians, whereas TP53 mutations rates were significantly lower. The lack of actionable hotspot mutations argue strongly for the need to comprehensively characterize gene mutations associated with OSCC for the development of new diagnostic and therapeutic tools.